A2B2 Porphyrin dyes for photodynamic anticancer and antimicrobial therapy - Nobatana, Vuyokazi (Rhodes University, 2026)
The search for alternative treatments and non-toxic photosensitiser drugs that can effectively produce cytotoxic reactive oxygen species for biomedical applications, such as in alternative photodynamic therapy (PDT) for cancer treatment and photodynamic antimicrobial therapy (aPDT) for drug-resistant bacteria treatment, is increasing. This thesis reports on the synthesis, characterization, and photo physiochemical properties of A2B2 asymmetrical porphyrins. The synthesized porphyrins were conjugated to gold nanoparticles (AuNPs) and gold-coated silica nanoparticles (AuSiO2) as potential photosensitizers for photodynamic anticancer and antibacterial therapy. The asymmetrical porphyrin complexes (1) 10,20-di(thiophene-2-yl)-5,15-diyl) dimorpholine porphyrin, complex (3) 5,15-Bis(4-(methylthio) phenyl)-10,20-di(pyridine-4-yl) porphyrin and their zinc derivates were conjugated on both AuNPs and AuSiO2NPs through the Au-sulfur/nitrogen bond. The effect of the zinc metal was studied by comparing complex 1 to its zinc complex (2) and complex 3 to its zinc complex (4). It was observed that the zinc complexes had better singlet oxygen production as compared to their unmetalled complexes (1 and 3). The photothermal activity of AuNPs and their conjugates were investigated, and a temperature increase in the porphyrins upon conjugation was observed. The lipophilicity and hydrophilicity of the porphyrins were also studied; complexes (3 and 4) with nitrogen substituents were found to be more lipophilic and porphyrin complexes (1 and 2) with oxygen substituents were found to be more hydrophobic. It was observed that the conjugation of porphyrins to the NPs enhanced the singlet oxygen quantum yield, PDT and aPDT activity. AuNPs conjugates overall had PDT and aPDT activity when compared to AuSiO2 conjugates.
Keywords: Uncatalogued